Standardising visual control devices for Tsetse: East and Central African Savannah species Glossina swynnertoni, Glossina morsitans centralis and Glossina pallidipes. - Mechtilda Byamungu; Tusevo Zacarie; Alexis Makumyaviri M'Pondi; Philémon Mansinsa Diabakana; Andrew McMullin; Thomas Kröber; Steve Mihok; Patrick M Guerin (Public Library of Science (PLoS), 2018)
BACKGROUND:This study focused on the savannah tsetse species Glossina swynnertoni and G. morsitans centralis, both efficient vectors of human and animal trypanosomiasis in, respectively, East and Central Africa. The aim was to develop long-lasting, practical and cost-effective visually attractive devices that induce the strongest landing responses in these two species for use as insecticide-impregnated tools in population suppression. METHODS AND FINDINGS:Trials were conducted in different seasons and years in Tanzania (G. swynnertoni) and in Angola and the Democratic Republic of the Congo (DRC, G. m. centralis) to measure the performance of traps (pyramidal and epsilon) and targets of different sizes, shapes and colours, with and without chemical baits, at different population densities and under different environmental conditions. Adhesive film was used to catch flies landing on devices at the remote locations to compare tsetse-landing efficiencies. Landing rates by G. m. centralis in both Angola and the DRC were highest on blue-black 1 m2 oblong and 0.5 m2 square and oblong targets but were not significantly different from landings on the pyramidal trap. Landings by G. swynnertoni on 0.5 m2 blue-black oblong targets were likewise not significantly lower than on equivalent 1 m2 square targets. The length of target horizontal edge was closely correlated with landing rate. Blue-black 0.5 m2 targets performed better than equivalents in all-blue for both G. swynnertoni and G. m. centralis, although not consistently. Baiting with chemicals increased the proportion of G. m. centralis entering pyramidal traps. CONCLUSIONS:This study confirms earlier findings on G. swynnertoni that smaller visual targets, down to 0.5 m2, would be as efficient as using 1 m2 targets for population management of this species. This is also the case for G. m. centralis. An insecticide-impregnated pyramidal trap would also constitute an effective control device for G. m. centralis.